Evaluación de la eficiencia de un proyecto piloto de inyección continua de vapor, usando las líneas de tendencias obtenidas de los KPIS y las propiedades del yacimiento de un estudio de caso (2018)
The present investigation initiated with the theoretical fundamentals related to steamflooding and the variables affecting the process, keeping in mind the work done in the first phase of this investigation by the researchers Lina Novoa y Gina Becerra, who determined the influential KPIs of the process. To determine the most accurate approach to utilize the data of the 56 oil fields studied, consigned in the database made by the authors, seven methodologies were studied, proposed by different authors in the past, to finally choose the two more proximate to the resolution of the planned objectives. These were the ones proposed by Bursell & Pittman in 1975, and by Chieh Chu in 1985, the first one making use of a graphical approximation, and the second one utilizing the linear regression as a method for the estimation of the steam/oil ratio. Based in this, these methodologies were taken, modified, and improved, to estimate the efficiency of a potential oil field to be steamflooded, where Palagua oil field was chosen in this project.